Primary cutaneous mucormycosis in a premature neonate treated conservatively with amphotericin B. Issue 1 (9th December 2021) - Vittitow, Stephany L.; Rusu, Corina A.; Abubakar, Maryam O.; Burnsed, Jennifer; Gru, Alejandro A.; Zlotoff, Barrett J.
Abstract: Cutaneous mucormycosis is a rare, often fatal fungal infection that most commonly affects patients with underlying immunosuppression but also can occur in premature neonates. We report the case of an extremely premature boy (<25 weeks) who developed primary cutaneous mucormycosis shortly after birth. Although surgical debridement has been a mainstay of treatment in combination with antifungal therapy, our patient was successfully treated with amphotericin B alone—the management only reported in three other cases to date. We present this case to highlight that prompt initiation of treatment with amphotericin B alone may be an appropriate alternative to surgical intervention, particularly in patients with non‐angioinvasive disease who are poor surgical candidates.